2015
DOI: 10.1597/13-074
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontic Rehabilitation of Congenital Auricular Defect: A Clinical Report

Abstract: This clinical report presents the prosthetic rehabilitation of a congenital auricular defect. The rehabilitation was initially performed with an adhesive retained silicone prosthesis. After careful evaluation of the patient's retentive needs, two endo-osseous craniofacial implants were placed in the mastoid region. After integration, an implant-retained silicone prosthesis was fabricated using a Hader bar with two ERA attachments, which restored the defect with good aesthetic and functional outcome. Prosthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…Defeitos auriculares representam grande complexidade para tratamento quando se trata de reconstrução cirúrgica, uma vez que essa estrutura possui uma ampla gama de detalhes anatômicos, o que pode exigir múltiplos procedimentos cirúrgicos além de grande habilidade profissional. Por isso, a reconstrução protética desse tipo de mutilação é frequentemente utilizada uma vez que, quando comparada ao método tradicional de reconstrução cirúrgica, apresenta resultados estéticos mais satisfatórios 4 . Além disso, tais próteses ISSN 2764-6289 são uma alternativa econômica quando comparadas à cirurgia de reconstrução, trazendo benefícios psicossociais para seus usuários 5 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Defeitos auriculares representam grande complexidade para tratamento quando se trata de reconstrução cirúrgica, uma vez que essa estrutura possui uma ampla gama de detalhes anatômicos, o que pode exigir múltiplos procedimentos cirúrgicos além de grande habilidade profissional. Por isso, a reconstrução protética desse tipo de mutilação é frequentemente utilizada uma vez que, quando comparada ao método tradicional de reconstrução cirúrgica, apresenta resultados estéticos mais satisfatórios 4 . Além disso, tais próteses ISSN 2764-6289 são uma alternativa econômica quando comparadas à cirurgia de reconstrução, trazendo benefícios psicossociais para seus usuários 5 .…”
Section: Introductionunclassified
“…A cirurgia plástica reconstrutiva parece ser a melhor abordagem de tratamento para defeitos na face na medida em que reconstrói estruturas perdidas com os tecidos biológicos do paciente. Contudo os resultados estéticos podem não ser satisfatórios para o paciente devido à alta complexidade cirúrgica, além da necessidade de vários procedimentos, necessidade de área doadora do enxerto e impossibilidade de avaliação da área afetada quando se trata de remoção oncológica 3,4 . Considerando a reconstrução auricular, a costela é comumente utilizada como área doadora, o que pode ocasionar problemas como pneumotórax 7 .…”
Section: Introductionunclassified
“…Many clinical studies have reported that the use of osseointegrated implants provides a satisfactory retention and improves the acceptance of auricular epithesis [12][13][14][15][16]. Further, craniofacial implants placed in the auricular region have been reported to have excellent survival rates [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, skin adhesives may lead to adverse tissue reactions, discoloration and deformation at edges of the epithesis, loss of adhesion because of perspiration, and difficulties in maintaining the position of the epithesis [5,12,[16][17][18]. On the other hand, craniofacial implants offer higher retention, allow easier positioning of the epithesis, and eliminate the use of adhesives, thus extending the epithesis survival [14,20]. Moreover, craniofacial implants placed in the auricular region have remarkable survival rates [17][18][19] even in irradiated patients.…”
mentioning
confidence: 99%
“…2 Compact splinted bar designs can use a single Hader bar and 2 cantilevering extraradicular attachments (ERA) at the terminal ends. 3 However, a new prosthesis generally needs to be fabricated every 1 to 2 years because of weathering and the wear and tear of the silicone. 4 Refabricating the prosthesis normally requires the patient to surrender the existing metal bar, which is then reused to fabricate a new polymethylmethacrylate (PMMA) resin housing for the retentive elements and the prosthesis.…”
mentioning
confidence: 99%